Pengaruh Supervisi Kepala Ruangan terhadap Kinerja Perawat Pelaksana di Ruang Rawat Inap Rumah Sakit Umum Wira Husada Kisaran Tahun 2025 - Diyan Afriyadi; Asriwati Asriwati; Ramadhani Syafitri Nasution (Jurnal Kesehatan Amanah, 2025)
Hospitals have the main responsibility in providing quality, effective, and efficient health services. The performance of the implementing nurse is an important indicator to ensure the quality of service and patient safety. The supervision of the head of the room as part of the managerial function includes planning, organizing, guidance, direction, supervision, evaluation, as well as recording and reporting, all of which are aimed at ensuring that nursing care is carried out according to standards. This study is focused on analyzing the influence of head of room supervision on the performance of implementing nurses in the inpatient room of Wira Husada Kisaran Hospital in 2025. The study used a quantitative approach with a cross sectional design. All 86 implementing nurses were sampled through the total sampling method. Data were collected with questionnaires on supervision and performance, then analyzed using univariate, bivariate with Chi-Square, and multivariate tests through multiple linear regression. The results showed that the functions of planning, supervision, evaluation, and recording and reporting had a significant effect on nurse performance (p<0.05). On the other hand, the organizing and directing functions did not have a significant effect, while guidance showed a negative direction. The most dominant variables were recording and reporting. Thus, it can be concluded that the supervision of the head of the room has a strategic role in improving nurse performance, so it is necessary to implement consistent, structured, and continuous supervision.